Graphics, animation and interactivity with flash 4.0 - Mohler, James L. (Albany, NY : Delmar, 2000)
1. Computer graphies 2. Computer animation 3. Interactive multimedia 4. Flash (computer file)
Includes bibliographical references and index.
Keywords: Flash (Computer file); Computer graphics; Computer animation; Interactive multimedia